(untitled) (Experimental biology, 2015)
The long-term plant regeneration technology developed by us can be use for obtain of somaclonal lines with stable inherited valuable traits. It was shown that some of these traits (dwarf, high grain mass, large grain, high grain yield) were fully maintained and increased in next generation of Otan and Celinnaya 3C cvs. somaclonal lines. The differences somaclonal lines as compared to the original variety and between themselves were revealed by the use of PCR analysis with IRAP-markers.